A Comparison of BPMN and UML 2.0 Activity Diagrams - Peixoto, Daniela C. C.; Batista, Vitor A.; Atayde, Ana P.; Borges, Eduardo P.; Resende, Rodolfo F.; Pádua, Clarindo Isaías P. S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2008: Anais do VII Simpósio Brasileiro de Qualidade de Software, 2008)
Interest in evaluating Business Process Modeling Languages has widespread, in part due to the increase of the number of languages available for this purpose. Several works on the evaluation of BPMLs are available. Their evaluation are mainly based on perspectives centered in modeling experts. In this paper, we address the readability perspective of two BPMLs (UML 2.0 and BPMN) for people not familiar with process modeling. The UML can be tailored for purposes beyond software modeling and offers Activity Diagrams for business process modeling. BPMN was designed for modeling business process and has a primary goal of being understandable by all business stakeholders. We compared undergraduates (freshmen) understanding of business process modeled in BPMN and UML 2.0 Activity Diagrams. Our results are interesting, since we were able to find that these two languages do not have significant differences, despite BPMN readability design goals.